Observations on the biology of Afrotropical Hesperiidae (Lepidoptera). Part 12. New information and corrections - Cock, Matthew J. W.; Congdon, T. Colin E.; Collins, Steve C. (Zootaxa, 2017)
Based mainly on the authors’ observations, information additional to the authors’ earlier papers on the biology of Afrotropical Hesperiidae is reported, including Pyrrhochalcia iphis (Drury), Pyrrhiades aeschylus (Plötz), Coeliades chalybe chalybe (Westwood), C. ramanatek ramanatek (Boisduval), C. libeon (Druce), Tagiades insularis Mabille, Abantis bamptoni Collins & Larsen, Apallaga spp. of the galenus clade, Platylesches morigambia Larsen, P. panga Evans, P. picanini (Holland), P. rasta Evans, and Prosopalpus styla Evans.  The larval ectoparasitoid Eulophidae from our rearing are revisited and grouped into seven morphospecies, including Stenomesius japonicus (Ashmead).  The phylogeny of the Hesperinae incertae sedis is discussed in light of recent work on the phylogeny of the Hesperiidae.  Apallaga handmani (Collins & Congdon) stat rev. is removed from synonymy of A. biseriata maculata (Hampson) and accepted as a good species based on barcode and biology differences.